2013
DOI: 10.1089/scd.2013.0013
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-2/-4 Upregulation Promoted by Endothelial Cells in Coculture Enhances Mouse Embryoid Body Differentiation

Abstract: Endothelial cells (ECs) provide inductive signals for cell differentiation in vivo. However, it is unknown if these cells promote such differentiation in vitro and the signals involved. We investigated whether ECs are able to enhance the differentiation of the three germ layers and the underlying mechanisms. We established a coculture system of mouse embryoid bodies (EBs) and ECs. Then, we analyzed the expression of markers representative of the three germ layers, such as PDX-1, proinsulin, insulin1 (endoderm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In the model using mouse EBs, we observed that ECs promote up-regulation of BMPs within EBs [53] . However, the target cells that produce these BMPs are still unknown.…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 88%
See 4 more Smart Citations
“…In the model using mouse EBs, we observed that ECs promote up-regulation of BMPs within EBs [53] . However, the target cells that produce these BMPs are still unknown.…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 88%
“…The role of BMPs in pancreas development has also been explored previously [72,93] . We demonstrated that HMECs or mouse dermis as well as mouse AECs expressed BMPs and that BMP-2 and BMP-4 increased the phosphorylation levels of SMAD1,5,8 in pancreatic progenitors and beta-like cells derived from mouse ESCs [52,53,94] . These findings together with previous works pointed out the important role of ECs in beta-cell differentiation in vitro.…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 90%
See 3 more Smart Citations